Metabolic and Nutritional Consequences of Urinary Diversion Using Intestinal Segments to Reconstruct the Urinary Tract - Roth, Joshua D.; Koch, Michael O. (Urologic clinics of North America, 2018)
Intestinal segments in various forms have been used to reconstruct the urinary tract since the mid-1800s. Currently, many different forms of continent and incontinent diversion options exist. Incorporating bowel mucosa within the urinary tract leads to predictable metabolic and nutritional consequences. The use of ileum or colon can cause a hyperchloremic metabolic acidosis, vitamin B12 deficiency, osteoporosis, fat malabsorption, urinary calculi, and ammoniagenic encephalopathy. Due to metabolic and nutritional consequences associated with the use of jejunum and gastric segments, the use of these bowel segments is not recommended.